Banks' Portfolio of Government Debt and Sovereign Risk - António Afonso; José Alves; Sofia Monteiro (Center for Economic Studies and ifo Institute (CESifo), 2023)
We analyze domestic, foreign, and central banks holdings of public debt for 31 countries for the period of 1989-2022, applying panel regressions and quantile analysis. We conclude that an increase in sovereign risk raises the share of domestic banks' portfolio of public debt and reduces the percentage holdings in the case of central banks. Better sovereign ratings also increase (decrease) the share of commercial (central) banks' holdings. Furthermore, the effects of an increment in the risk for domestic investors have increased since the 2010 financial crisis.
Keywords: C21; E58; G24; G32; H63; 330; banking; sovereign debt; sovereign risk; financial crisis; ratings